Synthesis of novel perillyl–dihydropyrimidinone hybrids designed for antiproliferative activity. Issue 9 (23rd August 2018) - Vendrusculo, Vinicius; de Souza, Vanessa P.; M. Fontoura, Luiz Antônio; M. D'Oca, Marcelo G.; Banzato, Thais P.; Monteiro, Paula A.; Pilli, Ronaldo A.; de Carvalho, João Ernesto; Russowsky, Dennis
Abstract : A series of fifteen novel dihydropyrimidinone hybrid compounds were synthesized in good yields via a multicomponent reaction combined with the Huisgen reaction. Abstract : A series of fifteen novel dihydropyrimidinone hybrid compounds were synthesized in good yields via a multicomponent reaction combined with the Huisgen reaction. The antiproliferative activity was investigated against nine tumor cell lines, and four hybrid compounds (TGI < 10 μM) showed promising antiproliferative activity against the tumor cell lines OVCAR-3 (ovarian), UACC-62 (melanoma) and U251 (glioma). Several hybrid compounds assayed have high TGI values (TGI 147.92–507.82) for the human keratinocyte cell line (HaCat), which reveals selectivity to cancer cells.